On the robust drivers of public debt in Africa: Fresh evidence from Bayesian model averaging approach - Madow Nagou; Nimonka Bayale; Brigitte Kanga Kouassi (Cogent Economics & Finance, 2021)
While economic theory suggests a wide range of potential drivers of public debt, there is little consensus regarding the most relevant ones. This paper analyzes the determinants of the public debt in Africa. This is done by adopting a Bayesian Model Averaging (BMA) approach applied to data of 51 African countries, spanning the period 1990-2018. Our results suggest that, among the set of twenty-seven (27) regressors considered, those reflecting international financial and institutional conditions as well as internal economic prospects tend to receive high posterior inclusion probabilities. Then, the study explores the effect of these regressors on public debt by employing the fixed effects (FE) and the system Generalized Method of Moments (GMM) estimators. The results reveal that, foreign aid, fiscal deficit, trade openness, military expenditure, interest and exchange rates, debt-service, domestic credit, government stability index, political regime type and socio-economic crises are the main and robust drivers of public debt accumulation in African countries. These findings are robust to changes in the model specification, the inclusion of socio-economic crises and regional heterogeneities.
Keywords: C11; C23; F34; N27; 330; Africa; Bayesian model averaging; panel data modelling; public debt